Pertumbuhan dan Produksi Tanaman Melon (Cucumis melo L) di Tanah Ultisol dengan Penambahan Pupuk Organik Cair (POC) Kulit Nanas - Ratna Santi; Sitti Nurul Aini; Nopan Darmawan (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2018)
Plant Growth and production of melon is affected by fertilizer so that alternative application of technology can be used liquid organic fertilizer (LOF) from pineapple peel. The purpose of this research is to know the effect ofliquid organic fertilizer on growth and production of melon plants in ultisol soil. Experimental methods used with single factor Randomized Block Design with 7 treatment levels were: inorganic fertilizer, 20 mL / 1 liter of water, 35 mL / 1 liter of water, 50 mL / 1 liter of water, P4 65 mL / 1 liter of water , P5 80 mL / 1 liter of water and 95 mL / 1 liter of water. The results of this study indicate the use of liquid organic fertilizer (LOF) does not gave a real effect on the growth and production of melon plants. Growth of melon plants treated 20 mL / 1 liter of water tend to be better while for production tend to be better at treatment 35 mL / 1 liter water.